CCAFS Scenarios Guide the Cambodian Climate Change Priorities Action Plan for Agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
In Cambodia, agriculture plays an important role in poverty reduction, employment and national development goals, with 85% of the labour force still engaged in agriculture. However, the country’s agricultural sector is highly sensitive to the impacts of climate change, requiring urgent action. In response, the Cambodian government launched its 2014-2018 Climate Change Priorities Action Plan (CCPAP), to convert financial resources and key practices into focused action. CCPAP has a strong focus on climate-smart agriculture, which is to be incorporated at the sub-national and community level.